(untitled) (World Economics and Finance Bulletin, 2024)
The research aimed to study the impact of using blockchain technology to improve tracking the movement of funds in supply chains in Iraqi commercial banks. The research population consisted of Iraqi commercial banks, with the Baghdad Commercial Bank chosen as the research sample. Among the most important results was that the application of blockchain technology improved the financial performance of the Commercial Bank of Baghdad and worked to achieve transparency and security in completing financial transactions. One of the prominent proposals was that accountants and auditors must delve deeply into blockchain technology because the design of financial systems will require financial experts who combine financial sciences with in-depth knowledge of technology.